OCURRENCIA DE Macrolophus praeclarus (DISTANT) (HEMIPTERA: MIRIDAE) EM EL ESTADO DE SÃO PAULO, BRASIL - Soto, Saúl Sánchez; Nakano, Octavio (REVISTA DE AGRICULTURA, 2015)
OCURRENCIA DE Macrolophus praeclarus (DISTANT) (HEMIPTERA: MIRIDAE) EM EL ESTADO DE SÃO PAULO, BRASIL